Correction: Effect of Ru substitution on the physical properties of La0.6Pr0.1Sr0.3Mn1−xRuxO3 (x = 0.00, 0.05 and 0.15) perovskites. Issue 54 (13th June 2015) - Zaidi, N.; Mnefgui, S.; Dhahri, J.; Hlil, E. K.
<x xml:space="preserve">Abstract</x> Correction for 'Effect of Ru substitution on the physical properties of La0.6Pr0.1Sr0.3Mn1−xRuxO3 (x = 0.00, 0.05 and 0.15) perovskites' by N. Zaidi et al., RSC Adv., 2015, 5, 31901–31909.